Pulse Wave Velocity Predicts Response to Renal Denervation in Isolated Systolic Hypertension. Issue 5 (17th May 2017) - Fengler, Karl; Rommel, Karl‐Philipp; Hoellriegel, Robert; Blazek, Stephan; Besler, Christian; Desch, Steffen; Schuler, Gerhard; Linke, Axel; Lurz, Philipp
Abstract : Background: Renal sympathetic denervation seems to be less effective as a treatment for hypertension in patients with isolated systolic hypertension, a condition associated with elevated central arterial stiffness. Because isolated systolic hypertension can also be caused by wave reflection or increased cardiac output, a more differentiated approach might improve patient preselection for renal sympathetic denervation. We sought to evaluate the additional predictive value of invasive pulse wave velocity for response to renal sympathetic denervation in patients with combined versus isolated systolic hypertension. Methods and Results: Patients scheduled for renal sympathetic denervation underwent additional invasive measurement of pulse wave velocity and pulse pressure before denervation. Blood pressure was assessed via ambulatory measurement at baseline and after 3 months. In total 109 patients (40 patients with isolated systolic hypertension) were included in our analysis. After 3 months, blood pressure reduction was more pronounced among patients with combined hypertension compared with patients with isolated systolic hypertension (systolic 24‐hour average 9.3±10.5 versus 5.0±11.5 mm Hg, P =0.046). However, when stratifying patients with isolated systolic hypertension by invasive pulse wave velocity, patients in the lowest tertile of pulse wave velocity had comparable blood pressure reduction (12.1±12.6 mm Hg, P =0.006) despite lower baseline blood pressure than patients with combined hypertension (systolic 24‐hour average 154.8±12.5 mm Hg in combined hypertension versus 141.2±8.1, 148.4±10.9, and 150.5±12.7 mm Hg, respectively, by tertiles of pulse wave velocity, P =0.002). Conclusions: Extended assessment of arterial stiffness can help improve patient preselection for renal sympathetic denervation and identify a subgroup of isolated systolic hypertension patients who benefit from sympathetic modulation.